2009
DOI: 10.1111/j.1600-6143.2008.02493.x
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Introduction of Reduced-Dose Tacrolimus, and Renal Function in Liver Transplantation: The ‘ReSpECT’ Study

Abstract: We report a multicenter, prospective, randomized, open-label trial investigating the effect of lower levels and delayed introduction of tacrolimus on renal function in liver transplant recipients. Adult patients with good renal function undergoing primary liver transplant were randomized to either: group A (standarddose tacrolimus [target trough levels >10 ng/mL] and corticosteroids; n = 183); group B (mycophenolate mofetil [MMF] 2g/day, reduced-dose tacrolimus [target trough levels ≤8 ng/mL], and corticostero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
198
2
8

Year Published

2010
2010
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 260 publications
(216 citation statements)
references
References 34 publications
8
198
2
8
Order By: Relevance
“…[16][17][18] The results of these studies are concordant and show that patients receiving reduced-dose CNI regimens have improved renal function 6 months to 1 year after transplantation in comparison with those receiving the standard-dose regimen (Table 1). Compensation for CNI minimization was generally achieved with the addition of mycophenolate mofetil (MMF).…”
Section: Early Cni Minimizationmentioning
confidence: 76%
See 2 more Smart Citations
“…[16][17][18] The results of these studies are concordant and show that patients receiving reduced-dose CNI regimens have improved renal function 6 months to 1 year after transplantation in comparison with those receiving the standard-dose regimen (Table 1). Compensation for CNI minimization was generally achieved with the addition of mycophenolate mofetil (MMF).…”
Section: Early Cni Minimizationmentioning
confidence: 76%
“…In these studies, the target trough level of tacrolimus for the patients on the reduced-dose regimen was less than 8 ng/mL (10-15 ng/mL for the standard-dose group). 17 In one study, the best results in terms of renal function were observed in the group receiving induction with anti-IL-2R antibodies plus reduced-dose tacrolimus. 17 However, in another controlled study, reduced-dose tacrolimus without induction or the delayed introduction of CNIs was also associated with improved renal function in comparison with standard-dose tacrolimus.…”
Section: Early Cni Minimizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Th e study had a few limitations, however, namely the use of estimated GFR calculated with the Cockcroft-Gault formula, and the fact that a signifi cant number of patients were withdrawn from the high dose group. However, it importantly demonstrated that the tailoring of an immunosuppressive regimen can have a signifi cant impact on nephrotoxicity without detrimental eff ects on graft function or patient survival [54].…”
Section: Orthotopic Liver Transplantationmentioning
confidence: 99%
“…Th e ReSpECT study compared standard tacrolimus dosing and steroids; lowdose tacrolimus plus steroids; and delayed introduction and low-dose tacrolimus plus steroids plus mycophenolate moefi til. Th e authors demonstrated reduced nephrotoxicity in the delayed, low dose tacrolimus group [54]. Daclizumab, a monoclonal antibody, was used to provide immunosuppressive cover during the delayed period before the introduction of tacrolimus.…”
Section: Orthotopic Liver Transplantationmentioning
confidence: 99%